Cutting plane algorithms for the inverse mixed integer linear programming problem - Wang, Lizhi (Operations research letters, 2009)
We present cutting plane algorithms for the inverse mixed integer linear programming problem (InvMILP), which is to minimally perturb the objective function of a mixed integer linear program in order to make a given feasible solution optimal.